Pemahaman Konsep Siswa Terhadap Materi Pecahan Melalui Pendekatan Kontekstual di Sekolah Dasar Kelas III - Khameswhari , Putri Flawlless Berlian; Anissa , Sania Dea; Zulkarnain , Ihwan; Amany, Abiyyah Rona (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2025)
Understanding the concept of fractions at the elementary school level remains a challenge for many students. Most of them struggle to grasp the meaning and application of fractions conceptually due to teaching approaches that are often abstract and disconnected from everyday life. This study aims to explore how contextual teaching can improve students’ conceptual understanding of fractions in a third-grade elementary classroom. The research employed a qualitative method with a case study approach, and data were collected through semi-structured interviews with several students who had experienced contextual-based learning. The findings reveal that contextual teaching helps students understand fractions as parts of a whole through concrete experiences, such as sharing food or objects. Students also showed greater enthusiasm and comprehension when learning was linked to real-life situations and involved the use of tangible media. In contrast, purely symbolic and abstract instruction was perceived as more difficult to understand. Therefore, contextual teaching is recommended as an effective strategy in elementary mathematics education, particularly for abstract topics like fractions.